Salvation and sin: Augustine, Langland, and fourteenth-century theology - Aers, David (Univ. of Notre Dame Press, 2009)
Augustinian prelude : conversion and agency -- Illustrating "modern theology" : sin and salvation in Ockham -- Thomas Bradwardine : reflections on De causa Dei contra Pelagium et de virtute causarum -- Remembering the Samaritan, remembering Semyuief : salvation and sin in Piers Plowman (the C version) -- Sin, reconciliation, and redemption : Augustine and Julian of Norwich